Collaboration of Local Wisdom and Contemporary Tourism as a Strategy for Sustainable Tourism Development in Batu City, East Java - Yuanita Yuanita; Derinta Entas; Rita Ritasari (Green Publisher Indonesia, 2025)
This research explores the critical need for integrating local wisdom and contemporary tourism as a comprehensive strategy for sustainable tourism development in Batu City, East Java. With rapid modernization threatening cultural authenticity, this study addresses the urgent challenge of balancing economic growth with cultural preservation and environmental sustainability. This *[A1] *research *[A2] explores the integration of local wisdom and contemporary tourism as a strategy for sustainable tourism development in Batu City, East Java. Batu City, known for its natural beauty and rapid tourism growth, faces challenges related to sustainability, cultural erosion, and social impacts. By emphasizing local traditions, community engagement, and the preservation of cultural heritage, this research highlights the importance of local wisdom in enhancing tourist experiences while ensuring environmental sustainability. The methodology involves qualitative analysis through interviews with stakeholders, observations, and literature reviews. The findings suggest that effective collaboration among government, businesses, and local communities is essential for creating a sustainable tourism ecosystem. The research proposes practical recommendations for policy and community involvement to strengthen local tourism based on cultural values.